Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1139/cjfas-2016-0265
|View full text |Cite
|
Sign up to set email alerts
|

Marine growth patterns of southern British Columbia chum salmon explained by interactions between density-dependent competition and changing climate

Abstract: Thirty-nine years of scale growth measurements from Big Qualicum River chum salmon (Oncorhynchus keta) in southern British Columbia demonstrated that competition and climate variation affect marine growth and age-at-maturity. A longitudinal study design that accounted for correlation among individuals revealed growth at all ages was reduced when the biomass of North American chum, sockeye (Oncorhynchus nerka), and pink salmon (Oncorhynchus gorbuscha) was high. When North Pacific Gyre Oscillation (NPGO) was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 66 publications
(119 reference statements)
3
25
0
1
Order By: Relevance
“…These include dramatic increases in the number of humans living near the Sound, increased marine mammal predation (Chasco et al, ), changes in hatchery salmon and steelhead production (HSRG, ), increased shoreline armouring (Habitat Strategic Initiative et al, ; Morrison et al, ), changes in the frequency of El Nino events (Wolter & Timlin, ), changes in herring, other forage fish, and jellyfish abundance and distribution (Greene, Kuehne, Rice, Fresh, & Penttila, ; Siple & Francis, ; Siple et al, ) and increased total salmon abundance in the Sound (as reported here). Each of these factors may have influenced growth and feeding conditions and thus body size of Puget Sound salmon and steelhead in a variety of ways, as they have been shown for these species in other areas within and outside the Salish Sea (Debertin et al, ; Jeffrey et al, ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These include dramatic increases in the number of humans living near the Sound, increased marine mammal predation (Chasco et al, ), changes in hatchery salmon and steelhead production (HSRG, ), increased shoreline armouring (Habitat Strategic Initiative et al, ; Morrison et al, ), changes in the frequency of El Nino events (Wolter & Timlin, ), changes in herring, other forage fish, and jellyfish abundance and distribution (Greene, Kuehne, Rice, Fresh, & Penttila, ; Siple & Francis, ; Siple et al, ) and increased total salmon abundance in the Sound (as reported here). Each of these factors may have influenced growth and feeding conditions and thus body size of Puget Sound salmon and steelhead in a variety of ways, as they have been shown for these species in other areas within and outside the Salish Sea (Debertin et al, ; Jeffrey et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Reduced body size of Pacific salmon has been linked to a variety of factors including fisheries-induced evolution (Fukuwaka & Morita, 2008;Kendall, Dieckmann, Heino, Punt, & Quinn, 2014), hatchery practices (Hankin, Fitzgibbons, & Chen, 2009;Swain, Riddell, & Murray, 1991), environmental and climate conditions (Debertin et al, 2017;Jeffrey et al, 2017;Morita & Fukuwaka, 2007), density-dependent effects (Ruggerone & Irvine, 2018) and increased natural mortality (e.g. predation by killer whales; Ohlberger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) due to predator sheltering (i.e., strength in numbers) and (2) a negative relationship in the offshore environment (Debertin et al. ; Yasumiishi et al. ) due to resource competition.…”
Section: Discussionmentioning
confidence: 99%
“…; Debertin et al. ). The hatchery organizations’ stakeholders are the licensed commercial fishermen that own limited‐entry salmon permits for the region and directly benefit economically from hatchery production by capturing these fish as they return to the hatchery as mature adults.…”
mentioning
confidence: 97%